Amplifying children’s leadership roles and voice in decision-making through co-production in outside of school hours care: qualitative findings from the connect promote and protect program - Milton, Alyssa C.; Ballesteros, Kristin; Hernandez, Helen; Hwang, Yenni; Glozier, Nick; McClean, Tom; LaMonica, Haley M.; Thorpe, Karen; Hickie, Ian B. (Frontiers in Education, 2025)
BackgroundThere is scant research examining evidence-based processes and practices that delineate how to include the voices of children in service design and delivery in school age care environments such as Outside of School Hours Care (OSHC). A possible structure to support children to share leadership in design of their OSHC program and have a meaningful voice in decision-making is co-production, whereby children and their OSHC communities have the opportunity to co-plan, co-design, co-deliver, and co-evaluate OSHC program activities. The Connect Promote and Protect Program (CP3), a social connection and wellbeing program that provides a structured method of co-producing with children, educators, and their OSHC communities, is examined.ObjectivesThis study aimed to explore the response to a co-production approach in OSHC settings as part of participation in the CP3.MethodsQualitative interviews and focus groups were conducted with 12 OSHC staff (educators, coordinators, managers, and volunteers) and 12 children attending OSHC as part of a wider mixed-methods implementation-effectiveness stepped-wedge trial of CP3 in 12 OSHC services located in urban and regional areas of New South Wales, Australia. Participants undertook semi-structured interviews/focus groups via multiple communication platforms (face-to-face, phone, and video-conferencing platforms). A representative research team (including researchers, OSHC educators/coordinators, OSHC administrators, clinicians, and parents of children in OSHC) used an inductive thematic analysis process. Two researchers undertook iterative coding using NVivo12 software, with themes developed and refined in ongoing team discussion.ResultsThe analysis identified nine sub-themes that related to child co-production and voice in CP3, which were organised into two super-ordinate themes: (1) processes that enable child agency and voice and (2) the impact of child agency and voice. Process related sub-themes included the following: co-production (ko-production) as a key driver; high-quality programming practice in a demanding environment; structure balanced with flexibility; the importance of being agile and having a willingness to adjust; and implementation factors supporting child voice. The impact related sub-themes included the following: empowerment of children through meaningful engagement; we all have a role in the team (a space for growing leadership skills); a spark through engagement and enjoyment; and being and belonging (the impact on children’s social and emotional wellbeing).ConclusionThis is the first known qualitative study to examine the use and impact of co-production processes in OSHC—where children not only co-design but also co-plan, co-deliver, and co-evaluate the activity programming alongside OSHC educators and their communities. The findings indicate that the co-production process provides a structured, yet flexible, way of supporting children’s voice and leadership even when delivered in diverse types of OSHC settings.